1999
DOI: 10.1002/1531-8249(199908)46:2<224::aid-ana12>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Classification of sporadic Creutzfeldt‐Jakob disease based on molecular and phenotypic analysis of 300 subjects

Abstract: Phenotypic heterogeneity in sporadic Creutzfeldt-Jakob disease (sCJD) is well documented, but there is not yet a systematic classification of the disease variants. In a previous study, we showed that the polymorphic codon 129 of the prion protein gene (PRNP), and two types of protease-resistant prion protein (PrP(Sc)) with distinct physicochemical properties, are major determinants of these variants. To define the full spectrum of variants, we have examined a series of 300 sCJD patients. Clinical features, PRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

70
1,006
11
85

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 401 publications
(1,172 citation statements)
references
References 31 publications
70
1,006
11
85
Order By: Relevance
“…Neuropathological review of these two earlier cases has found changes in the brain consistent with sporadic CJD; full clinical and genetic data are not available on these cases, but neither showed evidence of PrP RES accumulation in lymphoid tissues. The lack of characteristic neuropathology of vCJD in the brain, the absence of detectable PrP in the tonsil appendix and spleen, together with a PrP RES type 1 pattern in the cerebral cortex all provide supportive evidence for this being a case of sporadic CJD, similar to the other rare cases occurring in valine homozygotes with a type 1 PrP RES 3. A less likely explanation is that this case may represent bovine spongioform encephalopathy (BSE) infection in a valine homozygous person without the characteristic pattern of PrP glycosylation occurring in BSE and related disorders in animals and humans 5.…”
mentioning
confidence: 59%
“…Neuropathological review of these two earlier cases has found changes in the brain consistent with sporadic CJD; full clinical and genetic data are not available on these cases, but neither showed evidence of PrP RES accumulation in lymphoid tissues. The lack of characteristic neuropathology of vCJD in the brain, the absence of detectable PrP in the tonsil appendix and spleen, together with a PrP RES type 1 pattern in the cerebral cortex all provide supportive evidence for this being a case of sporadic CJD, similar to the other rare cases occurring in valine homozygotes with a type 1 PrP RES 3. A less likely explanation is that this case may represent bovine spongioform encephalopathy (BSE) infection in a valine homozygous person without the characteristic pattern of PrP glycosylation occurring in BSE and related disorders in animals and humans 5.…”
mentioning
confidence: 59%
“…According to Parchi et al ,35 in sporadic CJD disease different subtypes exist. As described in detail by Zerr et al ,36 the typical clinical phenotype with rapidly progressive dementia, myoclonus and typical EEG and CSF findings is present in about 70% of patients with CJD.…”
Section: Discussionmentioning
confidence: 99%
“…As described in detail by Zerr et al ,36 the typical clinical phenotype with rapidly progressive dementia, myoclonus and typical EEG and CSF findings is present in about 70% of patients with CJD. In 10% of cases of CJD, disease duration is longer and patients often show extrapyramidal signs (MV2 subtype35 37). In these patients EEG does not show CJD typical PSWCs and testing for protein 14–3–3 yields inconsistant results 36.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the size of the protease-resistant core fragment, several isoforms of PrP Sc can be recognised by immunoblotting,4 most commonly a type 1 (21 kDa) or a type 2 isoform (19 kDa). The currently accepted classification for sporadic Creutzfeldt-Jakob disease (sCJD) combines the PrP Sc isotype with the presence of either methionine or valine at codon 129 of the prion protein to define six molecular subtypes that correspond to distinct clinical and neuropathological phenotypes 5. A smaller fragment of protease-resistant PrP Sc (7–8 kDa) is found in patients with Gerstmann-Sträussler-Scheinker disease (GSS), a genetic form of prion disease 6…”
mentioning
confidence: 99%